Exploration of sensitivity limit for graphene magnetic sensors. (November 2015) - Chen, Bingyan; Huang, Le; Ma, Xiaomeng; Dong, Lijun; Zhang, Zhiyong; Peng, Lian-Mao
Abstract: Graphene Hall elements (GHEs) with ultra-high sensitivity are fabricated based on chemical vapor deposition (CVD)-grown graphene, and then the sensitivity limit and the relative mechanism are explored. Through tuning the 2-D carrier concentration by applying back-gate voltage, GHE can reach its maximum current related sensitivity up to 2745 V/AT. A model considering both of electron and hole is developed to describe the sensitivity of GHEs well especially near the Dirac point. The maximum current sensitivity of GHEs is then proved to be inversely proportional to the residual carrier concentration in graphene on substrate, which is helpful to provide strategy for further optimizing GHEs. Compromise between performance and uniformity should be carried out as a GHE is used in practice.